An ion-tolerance collector AESNa for effective flotation of magnesite from dolomite. (15th August 2021) - Liu, Wengang; Sun, Wenhan; Liu, Wenbao; Dai, Shujuan; Duan, Hao; Zhou, Shijie; Qiu, Jingping
Graphical abstract: Highlights: AESNa separates magnesite from dolomite via flotation for the first time. EO groups improve the ion tolerance and solubility of AESNa. The selectivity of AESNa is improved due to ion tolerance. The effect of Ca ions on selectivity changed from negative to positive. Abstract: The separation of magnesite and dolomite has always been a difficult problem in flotation production, one of the reasons is that the dissolved Ca 2+ ions from dolomite weaken the anionic flotation selectivity. In this study, an ion-tolerance collector, sodium fatty alcohol polyoxyethylene ether sulfonate (AESNa), was used to weaken or eliminate the adverse effects of Ca 2+ . Micro-flotation tests, surface tension tests, Fourier transform infrared spectroscopy (FTIR) tests, X-ray photoelectron spectroscopy (XPS) tests, and density functional theory (DFT) calculations were carried out. The micro-flotation results showed that AESNa had a better collecting ability and selectivity under alkaline conditions, and the addition of Ca 2+ selectively inhibited approximately 15% recovery of dolomite. Additionally, AESNa successfully separated magnesite from dolomite in the presence of Ca 2+ and water glass (Na2 SiO3 ) for the first time. The mechanism analysis indicated that AESNa had a high surface activity and was chemically adsorbed on the mineral surface. The EO groups in AESNa complexed with Ca 2+ by electrostatic interactions and made it difficult for Ca 2+ to invade polar head groups, resulting in the flotation of magnesite not being affected. Additionally, the interaction between the sulfonic groups and CaOH + was weak and led to inhibition of the adsorption of AESNa on the surface of dolomite by a large amount of CaOH + . Therefore, AESNa can promise a wide range of application prospects in flotation production, and the ion tolerance of the collector becomes a key factor in improving the flotation selectivity of soluble minerals.